Endoscopic Ultrasound-Guided Biliary Drainage in Two Patients with Difficult Biliary Access - Libânio, D. (2019)
Submitted by José Pereira (jro.pereira@gmail.com) on 2019-08-27T08:37:55Z No. of bitstreams: 1 Endoscopic Ultrasound-Guided Biliary Drainage.pdf: 1020771 bytes, checksum: 293218c94d08ad7a39fd26fa8a310c10 (MD5)